PENGARUH KOMBINASI LEMAK-METANOL DENGAN RASIO BERBEDA PADA SIFAT-SIFAT PRODUK BIODIESEL BERBAHAN BAKU LEMAK SAPI BALI YANG MENGGUNAKAN KOH SEBAGAI KATALIS - Muhammad Irfan Said; Tejo Laksono; Andi Utami A.N. (Jurnal Ilmu dan Industri Peternakan, 2014)
ABSTRACT. The fat (tallow) of bali cattle is a by-product that have not been used. The fat of cattle lately has been developed as a raw material for biodiesel. The process of biodiesel has done through a trans-esterification process and requiring of catalyst. The ratio of fat-methanol will determine the quality of biodiesel. This study aims to identify the effect of combination of fatmethanol with different ratios on the properties of biodiesel products made from fat of bali cattle. The fat of abdominal of Bali cattle was used as main material. There are three types of ratios were applied, namely (1:3), (1:5) and (1:7). The study was carried out experimentally by the reaction esterification and trans-esterification and than KOH as a catalyst. The results of this study showed that the application of ratio of fat-methanol different (1:3), (1:5) and (1:7) showed no significant effect on the value of water content, kinematic viscosity and flash point. Implementation of ratio of fat-methanol (1:3) can be applied to obtain more efficient results with properties corresponding to the INS.